THE PARTICULARS OF THE FINANCIAL AUDIT IN THE FIELD OF EUROPEAN PROJECTS - BOGDAN RĂVAŞ (Annals of the University of Petrosani: Economics)
For the first programming period of accessing the European funds granted to Romania through the European Union budget, the financial auditing of European projects was mandatory, and in the second period it was declared optional for the beneficiaries of the funding. From the perspective of financial auditors, the market segment of services provided for European projects has become highly specialized and concentrated towards a very small number of local auditors and audit firms, who penetrate this market and accumulate the audit contracts awarded and the related significant revenues. Thus, a sustainable capacity to provide the requested services was formed, but there is a risk of threats to the auditors' independence due to the dependence on the income obtained through this activity. The regulation of the activity of financial auditors in this field is necessary and can be achieved through collaboration between professional bodies and management authorities or other bodies involved in the management, control and audit of European funds. By drafting a separate normative act on the mandatory financial audit of European projects, one can benefit from the standardization, stability and integrity of the activities carried out and obtain audit insurance, necessary for the protection against incorrect or illegal practices in accessing European funds. Considering the significant public interest presented by European funds, a higher degree of transparency, integrity and responsibility on the part of beneficiaries and financial auditors in the implementation of European projects contributes to ensuring the protection of the EU's financial interests. The transparency of the financial audit activity can be achieved by presenting the information related to the audited projects in transparency reports published by the financial auditors. The operational audit performed by internal public auditors and the operations audit performed by external public auditors have common elements with the financial audit performed by financial auditors, members of CAFR. These types of audit have similar objectives and are very similar in terms of the way the missions are carried out, being carried out at the location of the funding beneficiaries, by checking the original documents and inspecting the assets related to the projects. On this basis, audit methods and procedures, perfected through scientific research to be more effective in identifying errors and frauds, can be used in practice, both by financial auditors and by internal and external public auditors.